(3GdeUGHjM aj TQM GdeaGJjMs - (3GdHgHgGfj, GdCSJGP GdCcHQ, GdhMjO, eMeO HGbQ Hf eMeO Cced, (B1206 (3g`s ((3EHQGgje GdeMeOs)
(3ChdgG (B:s
(3bhdg dUMGM GdeJajVI gj UMjMI eYGhjI Hf YeGQ hGHf hgH (B... (3dc UdGI hbJGf hChd GdhbJ CaVdg hUMjMI YHO GHf SfGf Yfg (B..s
(3BNQgG (B:s
... (3GdGfSH dg TQYG WQa GdRfG ceG gh GdXGgQ heY Pdc HYV GdKeQGJ GdTQYjI jJMbb ajg eKd YOe JLhjR fcGM GdCH HfJg hGdCe GHfgG hEf cGf ef GdRfG ceG Mbb aj eMdg (B.. (3JeJ GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\49s
(3GdPQjYI (B21 - 53 (4037 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis